2020
DOI: 10.1007/s11244-020-01341-9
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalysed Vapour-Phase Hydrogenation of Furfural, Insights into Reactivity and Deactivation

Abstract: Furfural is a key bioderived platform molecule, and its hydrogenation affords access to a number of important chemical intermediates that can act as "drop-in" replacements to those derived from crude oil or novel alternatives with desirable properties. Here, the vapour phase hydrogenation of furfural to furfuryl alcohol at 180 °C over standard impregnated nickel catalysts is reported and contrasted with the same reaction over copper chromite. Whilst the selectivity to furfuryl alcohol of the unmodified nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…[13,14] An array of alternative metal catalysts have been used in the literature for the hydrogenation of furfural to furfuryl alcohol in both the liquid and vapour phase, examples being: Cu, Ni, Pd, Pt, Co, Rh, Ir and Ru. [10,[15][16][17][18][19][20][21][22] Pt has been shown previously to be highly active and selective at low reaction temperatures under a headspace hydrogen atmosphere in the liquid phase. [16] Additionally, Pt is also effective for the hydrogenation of furfural in the vapour phase and also under Ultra-High Vacuum (UHV) conditions on Pt(111).…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] An array of alternative metal catalysts have been used in the literature for the hydrogenation of furfural to furfuryl alcohol in both the liquid and vapour phase, examples being: Cu, Ni, Pd, Pt, Co, Rh, Ir and Ru. [10,[15][16][17][18][19][20][21][22] Pt has been shown previously to be highly active and selective at low reaction temperatures under a headspace hydrogen atmosphere in the liquid phase. [16] Additionally, Pt is also effective for the hydrogenation of furfural in the vapour phase and also under Ultra-High Vacuum (UHV) conditions on Pt(111).…”
Section: Introductionmentioning
confidence: 99%
“…Another adverse effect of SiO 2 dissolution might be related to the coking effect since the Si–OH groups may contribute to the polymerization of FAL or FA under reaction conditions. Indeed, the TG analysis (Figure S6B) on the spent catalyst showed a remarkable weight loss (3.5 wt %) at a temperature from 200 to 500 °C, which was much less than that in an early report …”
Section: Results and Discussionmentioning
confidence: 57%
“…Wei and co-workers found that high exposure of the Ni(111) plane in Ni/MMO-CO 3 promotes activated adsorption of both the furan ring and CO group and favors the production of a fully hydrogenated product. However, Ni catalysts always underwent deactivation with time on stream (TOS) either in the gas phase or in the liquid phase due to the coke formation by oligomerization and deoxygenation, regardless of the support categories (SiO 2 , TiO 2 , and CeO 2 ) . The authors proposed that tuning the selectivity of the nickel by expense of some of its high hydrogenation activity may be helpful for developing stable Ni catalysts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-noble metal catalysts are a promising alternative if they exhibit the same or better activity and selectivity as their precious metal counterparts [13]. Kathryn and co-workers reported the application of a Ni/SiO 2 catalyst for the selective hydrogenation of FF to FA with a selectivity of 50% at a high reaction temperature of 180 • C [14]. In another example, a Ni/Al 2 O 3 catalyst displayed poor FA selectivity, giving methylfuran (MF), tetrahydrofurfuryl alcohol (THFA), tetrahydrofuran (THF), and furan (FU) [15].…”
Section: Introductionmentioning
confidence: 99%